Hippocampal vascularization patterns: A high-resolution 7 Tesla time-of-flight magnetic resonance angiography study - Marco Spallazzi; Laura Dobisch; Andreas Becke; David Berron; Daniel Stucht; Steffen Oeltze-Jafra; Paolo Caffarra; Oliver Speck; Emrah Düzel (NeuroImage: Clinical, 2019)
Considerable evidence suggests a close relationship between vascular and degenerative pathology in the human hippocampus. Due to the intrinsic fragility of its vascular network, the hippocampus appears less able to cope with hypoperfusion and anoxia than other cortical areas. Although hippocampal blood supply is generally provided by the collateral branches of the posterior cerebral artery (PCA) and the anterior choroidal artery (AChA), different vascularization patterns have been detected postmortem. To date, a methodology that enables the classification of individual hippocampal vascularization patterns in vivo has not been established. In this study, using high-resolution 7 Tesla time-of-flight angiography data (0.3 mm isotropic resolution) in young adults, we classified individual variability in hippocampal vascularization patterns involved in medial temporal lobe blood supply in vivo. A strong concordance between our classification and previous autopsy findings was found, along with interesting anatomical observations, such as the variable contribution of the AChA to hippocampal supply, the relationships between hippocampal and PCA patterns, and the different distribution patterns of the right and left hemispheres. The approach presented here for determining hippocampal vascularization patterns in vivo may provide new insights into not only the vulnerability of the hippocampus to vascular and neurodegenerative diseases but also hippocampal vascular plasticity after exercise training. Keywords: 7 T MRI, Hippocampal vascularization, Hippocampus, MR angiography, Neuroanatomy